A Photobiodynamic therapy: a new alternative for the treatment of Melasma - Rivera, Zulay; Ollarves, Victor; Rivera, Ingrid; Lugo, Dennis Alexander; Hagel, Isabel (Aesthetic Medicine, 2024)
Introduction: Melasma is a common acquired disorder of facial hyperpigmentation with frequent recurrence after treatment. Objective: To evaluate the effect of a multimodal photodynamic therapy on the treatment of melasma. Methodology: A multimodal therapy that combines the topical application of antioxidant molecules, tyrosinase inhibitors, melanogenesis blockers, antioxidants, and anti-inflammatory molecules, with UV-free photomodulation based on HDD light (I.o. 530± 10 nm) and colloidal gold as photoactivator was applied to 28 female patients affected by melasma. The presence of defined brown spots of variable extension (melasma) and red areas (vascular alterations) on the face of the patients was evaluated before and 6 weeks after finishing the treatment. Wood’s lamp, VISIA system and 3D Digital Photography were used. The treatment was applied in 4 phases (peeling, photodynamic serum, HDD light and depigmenting mask) under medical supervision. Results: 28 volunteer patients, diagnosed with melasma, of Latino origin with a predominance of phototype III on the Fitzpatrick scale, participated in this study. 86% of the patients, in addition to melasma, exhibited red areas, indicative of vascular alterations. 75% of the patients had been previously treated in the last two years with other treatment modalities and exhibited a relapse. The 3D digital photographs showed that all the patients improved in the resolution of the spots after the treatment. The improvement was significant, decreasing both the brown hyperpigmented areas and the red vascularized areas. The values obtained on the VISIA scale by the total group of patients before and 6 weeks after completing the treatment confirmed a significant improvement (p<0.005) in terms of the resolution of UV spots, brown spots as well as in the red areas and better pigment distribution of the affected sensitive area. Conclusions: The results of this work are preliminary. However, they showed for the first time, that this therapeutic approach was effective, although necessary to evaluate the effect in these patients later in time, and did not cause any discomfort or inflammatory complications after its application, in any of the patients.